Influência da altura das garras dos pneus de um trator em área de plantio direto - Gabriel Filho, Antonio (2010)
This work was carried out to evaluate the performance of a farm tractor fitted with two sets of tires with high lugs and another set of tires with tallow lugs in straw without tillage (corn straw). The travel speeds used were approximately 4, 5, 6 and 7 km h-1 and a constant pulling force of 25 kN was fixed. Tractor traction, forward speed, slip and consumption of fuel were measured and drawbar power, the ratio between the consumption and power and traction coefficient were calculated. It was observed that the tractor performance was similar to high and low lug tire conditions, in an area covered with corn straw.